The evolving landscape of healthcare regulations in Vietnam: A critical review and recommendations - Thi Bao Anh Nguyen (Healthcare in Low-resource Settings, 2026)
This study examines the Vietnamese government's regulatory mechanisms for ensuring quality healthcare. Its primary objective is to analyze the evolution of Vietnam’s healthcare system, assess the effectiveness of current regulations, and provide evidence-based recommendations for future improvements. The research traces the historical development of healthcare policies and highlights key reforms that have shaped the current landscape. Through thematic and content analyses, the study explores complexities in healthcare access, including freedom of choice, health insurance participation, and coverage disparities. Despite notable progress, challenges remain, such as high insurance premiums, co-payment burdens, policy reform inefficiencies, and social security gaps. The government has introduced new health insurance strategies and innovative reimbursement mechanisms. Key recommendations include expanding health insurance coverage, enhancing support for medical practitioners, and leveraging digital health technologies. Addressing these systemic issues can help Vietnam create a more sustainable, equitable, and efficient healthcare system for its population.